Boiling in nanopores through localized Joule heating: Transition between nucleate and film boiling - Soumyadeep Paul; Wei-Lun Hsu; Yusuke Ito; Hirofumi Daiguji (Physical Review Research, 2022)
The transition from nucleate to film boiling on micro/nanotextured surfaces is of crucial importance in a number of practical applications, where it needs to be avoided to enable safe and efficient heat transfer. Previous studies have focused on the transition process at the macroscale, where heat transfer and bubble generation are activated on an array of micro/nanostructures. In the present study, we narrow down our investigation scale to a single nanopore, where, through localized Joule heating within the pore volume, single-bubble nucleation and transition are examined at nanosecond resolution using resistive pulse sensing and acoustic sensing. Akin to macroscale boiling, where heterogeneous bubbles can nucleate and coalesce into a film, in the case of nanopores also, patches of heterogeneous bubbles nucleating on the cylindrical pore surface can form a torus-shaped vapor film blanketing the entire pore surface. In contrast to conventional pool boiling, nanopore boiling involves a reverse transition mechanism, where, with increased heat generation, film boiling reverts to nucleate boiling. With increasing bias voltage across the nanopore, the Joule heat production increases within the pore, leading to destabilization and collapse of the torus-shaped vapor film.